2021
DOI: 10.1123/jsr.2019-0521
|View full text |Cite
|
Sign up to set email alerts
|

Validity and Reliability of Hand-Held Dynamometry for Abdominal Flexion Muscular Assessment

Abstract: Context: Abdominal musculature underpins core stability, which can allow for optimal performance in many activities of daily living (eg, walking and rising from a chair). Therefore, assessment of the abdominal muscles poses as an important consideration for clinicians in order to identify people at risk of injury or functional decline. Objective: This study aimed to build on the limited amount of knowledge surrounding abdominal muscle strength assessments by investigating the validity and reliability of hand-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Asymptomatic individuals. Eight studies evaluated the intra-rater reliability of HHD for trunk flexion, extension and side bending where the dynamometer was externally fixed [43,44,47,52,60] or held by the examiner [58,61,63]. All studies rated as sufficient for the COSMIN criteria for good measurement properties where the ICC ranged from 0.8 to1.00 except for flexion from supine position where ICC = 0.67 [63] and…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Asymptomatic individuals. Eight studies evaluated the intra-rater reliability of HHD for trunk flexion, extension and side bending where the dynamometer was externally fixed [43,44,47,52,60] or held by the examiner [58,61,63]. All studies rated as sufficient for the COSMIN criteria for good measurement properties where the ICC ranged from 0.8 to1.00 except for flexion from supine position where ICC = 0.67 [63] and…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…Six studies investigated criterion validity of the HHD compared to ID [43,52,58,60,63] with moderate quality evidence overall indicating moderate confidence in the criterion validity estimates of the HHD in measuring trunk flexion and extension strength. Only one study with extremely serious ROB revealed sufficient convergent validity of the HHD compared to Back-Check (BC) [44] with overall, very low quality evidence.…”
Section: Plos Onementioning
confidence: 99%
“…HHD showed good agreement (ICC=0.82) and good consistency (ICC=0.87). 21 It was observed that all HHD assessments are highly reliable. Thus, HHD is considered suitable for testing the isometric strength of lumbar muscles in clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…The abdominal flexion strength assessment has demonstrated good to excellent validity (ICC = 0.82) and reliability (ICC = 0.86) for the assessment of abdominal flexion strength. 22 No breaking procedure was used, participants performed 3 isometric efforts on each limb or 3 single isometric efforts of the abdominal flexion holding each effort for 3 seconds with the result in kilograms recorded. The highest value obtained for each limb and assessment were recorded.…”
Section: Methodsmentioning
confidence: 99%